Application of entomopathogenic fungus Beauveria brongniartii for management of chafer beetle of the white grub holotrichia serrata infesting rubber seedlings - Nehru C R; Jayarathnam K; Karnavar G K (Indian Journal of Natural Rubber Research, 1991)
The infectivity of the entomopathogenic fungus Beauveria brongniartii to adult beetles, which are responsible for the abundance and distribution of white grubs (H. serrata) in rubber nurseries, is reported. Longevity of the adult beetles of both sexes infected with B.brongniartii spreads from contaminated adults to healthy ones through mating contact. Release of the contaminated adults in the nursery was effective for biological suppression of H. serrata.
Keywords: Beauveria brongniartii; Holotrichia serrata; Rubber nurseries